2021
DOI: 10.1002/ccd.29525
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of in‐hospital cardiac arrest in COVID‐19 patients: A proportional prevalence meta‐analysis

Abstract: Background Limited epidemiological data are available on the outcomes of in‐hospital cardiac arrest (CA) in COVID‐19 patients. Methods We performed literature search of PubMed, EMBASE, Cochrane, and Ovid to identify research articles that studied outcomes of in‐hospital cardiac arrest in COVID‐19 patients. The primary outcome was survival at discharge. Secondary outcomes included return of spontaneous circulation (ROSC) and types of cardiac arrest. Pooled percentages wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Findings showed that the total rate of in-hospital CA was 9.39%. In line with this nding, a former study reported that the rate of in-hospital CA among patients with COVID-19 was 10% (9). Most participants suffered from at least one underlying disease, particularly diabetes mellitus, hypertension, cardiovascular disease, and cancer.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Findings showed that the total rate of in-hospital CA was 9.39%. In line with this nding, a former study reported that the rate of in-hospital CA among patients with COVID-19 was 10% (9). Most participants suffered from at least one underlying disease, particularly diabetes mellitus, hypertension, cardiovascular disease, and cancer.…”
Section: Discussionsupporting
confidence: 58%
“…A former study in this area reported that the rate of ROSC after CPR was 25.9% for out-of-hospital CA and 30.6% for in-hospital CA (25). Moreover, a meta-analysis on four studies on 621 patients with COVID-19 showed that the pooled prevalence of primary CPR success was 39% (95% CI: 21.0-59.0%) (9). The rate of primary CPR success in these two studies are much better than the rate in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analyses were performed using the random effect restricted maximum-likelihood (REML) model to calculate an unadjusted odds ratio (OR). "The random-effects model assumes that the studies included in the meta-analysis are a random sample of hypothetical study populations" [ 6 ]. The estimated effect size was reported as a point estimate and 95% confidence interval (CI) for all studies and separate sub-analyses of randomized controlled trials (RCTs) as well as retrospective cohort studies.…”
Section: Methodsmentioning
confidence: 99%